Recognition and Non-Recognition of a State Resulting from Secession: Case Studies of Annulled Status of the Turkish Cypriot Entity after its Declaration as "Turkish Republic of Northern Cyprus" and Kosovo - Kanellopoulos, Anastasios Nikolaos (HAPSc Policy Briefs Series, 2022)
This paper approaches the situation of a state’s recognition or non-recognition, in cases arising from secession. In particular, the international law will be presented, regarding the recognition of states that come from secession and have been created, either on the occasion of prohibited violence use, or for the sake of rehabilitation due to human rights violations. After that, the cases of the Turkish Cypriot annulled status entity after its declaration as the “Turkish Republic of Northern Cyprus” and Kosovo will be examined. The overview and legal evaluation of these two cases, can provide useful conclusions regarding the legalization of a state recognition that has resulted from secession.